High-stability UV viscosity-reducing adhesive tape and preparation method thereof

By using UV adhesive tape made of raw materials such as polyacrylic acid-butadiene resin and cholesterol fluoride, combined with crosslinked branched structure and composite photoinitiator, insufficient stability and residual glue in acid-base environment are solved. Problem, UV adhesive tape with high initial viscosity and good peeling effect is achieved.

CN119119906APending Publication Date: 2024-12-13ANHUI MINGXUN NEW MATERIAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411065810.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-05
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing UV adhesive tape is insufficient in acid-base environment, which can easily lead to residual glue on the product surface after high temperatures, and the use of photoinitiators leads to short storage life and easy yellowing.

Method used

UV-retardant pressure-sensitive adhesive layer made of polyacrylic acid-butadiene resin, cholesteric fluoride, leveling agent, photoinitiator and curing agent, introduces acid and alkali resistant through crosslinking branched structure and fluorine atoms. and use a composite photoinitiator to improve photoinitiation activity and efficiency and reduce residual glue.

Benefits of technology

UV adhesive tape with high stability, high initial viscosity in an acid-base environment, and good peeling effect after UV irradiation without residual glue is achieved, filling the defects in the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004979322940000051
    Figure BDA0004979322940000051
  • Figure BDA0004979322940000061
    Figure BDA0004979322940000061
Patent Text Reader

Abstract

The invention provides a high-stability UV viscosity-reducing adhesive tape and a preparation method thereof. The UV viscosity-reducing adhesive tape comprises a release layer, a UV viscosity-reducing pressure-sensitive adhesive layer and a base material layer, wherein the UV viscosity-reducing pressure-sensitive adhesive layer is prepared from the following raw materials in parts by mass: 70-80 parts of polyacrylic acid-butadiene resin, 15-40 parts of cholesterol fluoride, 2-5 parts of a flatting agent, 0.5-5 parts of a photoinitiator, 1-3 parts of a curing agent and 55-90 parts of a solvent; by introducing a cross-linked branched structure and fluorine atoms, the effects of acid and alkali resistance and high initial adhesion can be achieved; and the compound photoinitiator is selected, so that the photo-initiation activity and efficiency are improved, migration and polymerization are avoided in an acid-base environment, efficient initiation and rapid curing are realized after UV irradiation viscosity reduction, and the occurrence of adhesive residues is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pressure-sensitive adhesives, and in particular to a highly stable UV anti-viscosity tape and a preparation method thereof. Background Art

[0002] With the rapid development of science and technology, the demand for polymer materials in modern industry is also increasing. Acrylate, as a common material, is widely used in the fields of automobiles, construction, electronics, etc. UV anti-viscosity film, also known as anti-viscosity protective film, has excellent chemical resistance, temperature resistance and dimensional stability, reduces adhesive viscosity through UV light, high temperature and hot water, is recyclable, and can be widely used in the circuit board (FPC and PCB) industry, process, metal surface protection, electronics, industrial film and other surface protection fields to ensure that the products do not fall off or scatter, and reduce the breakage during cutting; at the same time, the viscosity of the tape is reduced after UV ultraviolet irradiation, and the products are easy to pick up.

[0003] At present, most of the anti-viscosity tapes on the market are UV anti-viscosity tapes, which means anti-viscosity tapes with high adhesion and good adhesion before UV irradiation, and with significantly reduced adhesion after UV irradiation, and easy to peel off. However, in the production process of the electronics industry, some processes involve acid and alkali, such as the touch panel process, where the glass needs to be sprayed or soaked with alkali liquid, and the chemical plating UBM process of the wafer. These production processes need to go through harsh acid and alkali environments; in today's advocacy of building an environmentally friendly society, more attention is paid to the research and development of UV curing anti-viscosity tape products and curing processes at home and abroad, and they are committed to providing more types of UV acrylic anti-viscosity tapes with good stability in acid and alkali environments, good bonding performance, and environmental protection and energy saving.

[0004] In view of this, Chinese patent number CN108300352A proposes an acid-base resistant UV anti-viscosity composition, a UV anti-viscosity film and a preparation method thereof. The acid-base resistant UV anti-viscosity composition is mainly made of the following raw materials by weight percentage: 25%-45% polyacrylate pressure-sensitive adhesive, 1%-20% multifunctional oligomer and / or multifunctional monomer, 0.1%-1.5% photoinitiator, 0.1%-2% curing agent and 30%-60% solvent. The UV anti-viscosity film comprises a substrate layer, a UV anti-viscosity film and a UV anti-viscosity film. The adhesive layer and the release film layer, wherein the UV anti-viscosity layer is obtained by coating the UV anti-viscosity composition on the surface of the substrate layer and baking. The UV anti-viscosity composition has high adhesion and high peeling force before UV irradiation, low adhesion and low UV peeling force after UV irradiation, and has excellent acid and alkali resistance. However, in the above patents, the acid and alkali resistant UV anti-viscosity composition prepared has the hidden dangers of short storage life and easy yellowing due to the use of photoinitiator, which reduces the use properties of the acid and alkali resistant UV anti-viscosity composition.

[0005] It can be seen from the above that if the adhesion and acid-base stability of the UV anti-viscosity tape are not balanced, residual adhesive will often appear on the surface of the product in an acid-base environment or after high temperature; therefore, it is an urgent problem to be solved in the art to provide a UV anti-viscosity tape solution that has high stability and high initial adhesion in an acid-base environment, good peeling effect after UV irradiation and no residual adhesive. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a highly stable UV anti-viscosity tape and a preparation method thereof, which is expected to have high stability and high initial adhesion in acidic and alkaline environments, and a UV anti-viscosity tape with good peeling effect and no residual adhesive after anti-viscosity reduction by UV irradiation, thereby filling the defects in the prior art.

[0007] The technical solution of the present invention:

[0008] In one aspect, the present invention provides a highly stable UV adhesive tape, the UV adhesive tape comprising a release layer, a UV adhesive pressure-sensitive adhesive layer and a substrate layer; wherein the UV adhesive pressure-sensitive adhesive layer is made of the following raw materials in parts by weight:

[0009] 70-80 parts of polyacrylic acid-butadiene resin, 15-40 parts of cholesteryl fluoride, 2-5 parts of leveling agent, 0.5-5 parts of photoinitiator, 1-3 parts of curing agent, and 55-90 parts of solvent.

[0010] In some embodiments, the polyacrylic acid-butadiene resin is a polymer obtained by copolymerization of acrylic acid and butadiene; the content of butadiene component in the polyacrylic acid-butadiene resin is 30-40%.

[0011] In some embodiments, the method for preparing the cholesterol fluoride comprises:

[0012] Step 1: Take 5-norbornene-2-yl chloride and heat it with 4-(trifluoromethyl)benzyl alcohol to obtain (5-norbornene-2-carboxylic acid)-4-(trifluoromethyl)benzyl ester, hereinafter referred to as intermediate 1;

[0013] Step 2: Intermediate 1 and cholesterol are added under acidic conditions to obtain cholesterol fluoride.

[0014] In some embodiments, the leveling agent is selected from any one of acrylic leveling agents, silicone leveling agents, and fluorocarbon leveling agents, or a combination of at least two thereof. For example, it can be selected from any one of EFKA3883, EFKA3886, EFKA3600, BYK366, BYK333, BYK307, and TEGOGlide410, or a combination of at least two thereof. The materials listed above are not limited to the materials listed above.

[0015] The photoinitiator belongs to a free radical initiator. This type of substance generates free radicals under ultraviolet light by absorbing energy of a certain wavelength to initiate double bond polymerization to form a stable colloid. In some embodiments, the photoinitiator is selected from benzil dimethyl ether, dialkoxy acetophenone, methyl benzoyl formate (MBF), 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone, 2,4,6-trimethylbenzoylphenylphosphine, 2,4,6-trimethylbenzoyldiphenylphosphine oxide (TPO), 2,4,6-trimethylbenzoyl ... The invention relates to a photoinitiator for preparing the photosensitive adhesive. The photoinitiator is any one of ethyl benzoylphenylphosphonate, benzophenone, 4,4'-bis(diethylamino)benzophenone, 2-isopropylthioxanthone (ITX) and 4-dimethylamino-ethyl benzoate (EDB), or a combination of at least two thereof; preferably, the photoinitiator is a mixture of 2-isopropylthioxanthone and 4-dimethylamino-ethyl benzoate; the photoinitiator activity and efficiency are improved by the composite photoinitiator, the photoinitiator does not migrate or polymerize in an acidic or alkaline environment, and the photoinitiator is efficiently initiated after the viscosity is reduced by UV irradiation, and the photoinitiator is quickly cured, thereby reducing the generation of residual adhesive.

[0016] In some embodiments, the curing agent is selected from any one or a combination of at least two of benzoyl peroxide, dicumyl peroxide, tert-butyl perbenzoate or 2,5-di(2-ethylhexanoyl peroxy)-2,5-dimethylhexane; the above materials are listed but not limited to the above materials, and commonly used curing agents can be used.

[0017] In some embodiments, the solvent is selected from any one or a combination of at least two of ethyl acetate, butyl acetate, methyl formate, ethyl formate, methyl acetate, propyl acetate, isopropanol, acetone, butanone, toluene, xylene, petroleum ether, n-hexane and cyclohexane.

[0018] In some embodiments, the UV viscosity-reducing pressure-sensitive adhesive layer is made of the following raw materials in parts by mass:

[0019] 70-80 parts of polyacrylic acid-butadiene resin, 20-30 parts of cholesterol fluoride, 2-3 parts of leveling agent, 0.5-3 parts of photoinitiator, 1-3 parts of curing agent, and 60-78 parts of solvent.

[0020] In some embodiments, the release layer and the substrate layer of the highly stable UV adhesive tape can be made of conventional materials; for example, the release layer is made of a silicone polyester release film or release paper; the substrate layer can be made of any one of PET, PI, PC, and PU, or a combination of at least two of them.

[0021] In some embodiments, the number and stacking method of release layers, UV viscosity-reducing pressure-sensitive adhesive layers and substrate layers are not limited by the present invention; for example, the highly stable UV viscosity-reducing tape can be a release layer, a UV viscosity-reducing pressure-sensitive adhesive layer and a substrate layer from top to bottom to make a single-sided tape; it can also be a release layer, a UV viscosity-reducing pressure-sensitive adhesive layer, a substrate layer, a UV viscosity-reducing pressure-sensitive adhesive layer and a release layer to make a double-sided tape; or other situations not exemplified in the present invention.

[0022] In some embodiments, the method for preparing the UV viscosity-reducing pressure-sensitive adhesive layer comprises:

[0023] Step 1: Add the leveling agent and photoinitiator to a vacuum centrifugal high-speed disperser, stir under vacuum, and dissolve completely;

[0024] Step 2: Add the polyacrylic acid-butadiene resin into the disperser in step 1, stir under vacuum, seal and let stand;

[0025] Step 3: Add the above-mentioned cholesterol fluoride and curing agent into a disperser, continue vacuum stirring, centrifuge and degas in a syringe, and vacuum seal with an aluminum foil bag to prepare the UV viscosity-reducing pressure-sensitive adhesive layer.

[0026] In some embodiments, the vacuum stirring in the preparation method has a stirring speed of 500-800 r / min, a stirring time of 3-5 min, and a vacuum degree of -0.05-(-0.08) MPa.

[0027] In some embodiments, the thicknesses of the release layer, the UV viscosity-reducing pressure-sensitive adhesive layer, and the substrate layer are 50±2 μm, 100±10 μm, and 25±2 μm, respectively.

[0028] On the other hand, the present invention also provides a method for preparing the UV anti-viscosity tape as described above, comprising:

[0029] A UV viscosity-reducing pressure-sensitive adhesive layer is coated on the surface of a substrate, and a release agent is coated on the outer side of the UV viscosity-reducing pressure-sensitive adhesive layer to prepare a release layer to obtain a UV viscosity-reducing tape; wherein the UV viscosity-reducing pressure-sensitive adhesive layer can be coated on one side or both sides of the substrate, for the convenience of unwinding and application according to the properties of the substrate.

[0030] Beneficial effects:

[0031] The present invention can achieve the effects of acid and alkali resistance and high initial adhesion by introducing a cross-linked branched structure and fluorine atoms; the composite photoinitiator is selected to improve the photoinitiator activity and efficiency, and it does not migrate or polymerize in an acidic or alkaline environment, and it can be efficiently initiated and quickly cured after UV irradiation to reduce viscosity, thereby reducing the generation of residual glue. DETAILED DESCRIPTION

[0032] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.

[0033] Unless otherwise specified, the chemical reagents used in the present invention are all commercially available analytically pure.

[0034] Preparation of Cholesteryl Fluoride

[0035] Step 1: Take 0.2 mol of 5-norbornene-2-yl chloride and add it into a three-necked flask, add 100 ml of tetrahydrofuran and mix well, slowly dropwise add 0.17 mol of 4-(trifluoromethyl)benzyl alcohol, stir at room temperature for 2 hours, then heat to 90° C. for 15 hours, filter and recrystallize to obtain (5-norbornene-2-carboxylic acid)-4-(trifluoromethyl)benzyl ester, hereinafter referred to as intermediate 1;

[0036] Step 2: Add 0.12 mol of cholesterol and 100 ml of solvent dimethyl sulfoxide into a round-bottom flask and stir evenly; then add 0.1 mol of intermediate 1 and 0.05 mol of sulfuric acid, heat to 60°C and react for 4 hours. After the reaction is completed, cool to room temperature, filter, wash with deionized water, and recrystallize with ethanol to obtain cholesterol fluoride.

[0037] IR (KBr, cm -1 ): 805, 1035, 1230, 1455, 1650, 2810, 3100, 3450; it can be seen that trifluoromethyl, double bond and ester group are grafted onto cholesterol fluoride, indicating that cholesterol fluoride is successfully synthesized.

[0038] Preparation of polyacrylic acid-butadiene resin

[0039] In a dry reaction container, add 100 ml of toluene, add acrylic acid and butadiene monomers to the solvent while stirring, the molar amounts of acrylic acid and butadiene monomers are 7 mol and 3 mol, respectively, stir evenly, then add 0.3 mol of diisopropylbenzene peroxide, polymerize at 80°C for 6 hours, and obtain polyacrylic acid-butadiene resin after extraction and recrystallization.

[0040] Preparation of highly stable UV-resistant pressure-sensitive adhesive layer

[0041] Step 1: Add the leveling agent and photoinitiator to a vacuum centrifugal high-speed disperser, stir at -0.05MPa vacuum and 600r / min for 5min, and dissolve completely;

[0042] Step 2: Add polyacrylic acid-butadiene resin into the disperser in step 1, stir at -0.05MPa vacuum and 600r / min for 5min, seal and let stand;

[0043] Step 3: Add the above-mentioned cholesterol fluoride and curing agent into a disperser, continue vacuum stirring, centrifuge and degas, and use an aluminum foil bag for vacuum plastic sealing to prepare the highly stable UV viscosity-reducing pressure-sensitive adhesive layer (hereinafter referred to as pressure-sensitive adhesive layer).

[0044] The formulations of different pressure-sensitive adhesive layers are shown in Table 1.

[0045] Table 1 Pressure-sensitive adhesive layer formula (unit: mass parts)

[0046]

[0047] Examples and Comparative Examples

[0048] The pressure-sensitive adhesive layer was coated on the upper and lower surfaces of the substrate (PET, Dongguan Tianyi Chemical Co., Ltd.), and then a release agent (JT-561) was coated on the outer sides of the two pressure-sensitive adhesive layers to prepare a release layer, and UV adhesive tapes were obtained. The thickness of the substrate layer was 50 μm; the thickness of the pressure-sensitive adhesive layer was 100 μm; and the thickness of the release layer was 50 μm. The specific details are shown in Table 2.

[0049] Table 2 Pressure-sensitive adhesive layers used in the examples and comparative examples

[0050] Example Pressure sensitive adhesive layer Comparative Example Pressure sensitive adhesive layer Example 1 Pressure sensitive adhesive layer 1 Comparative Example 1 Pressure sensitive adhesive layer 5 Example 2 Pressure sensitive adhesive layer 2 Comparative Example 2 Pressure sensitive adhesive layer 6 Example 3 Pressure sensitive adhesive layer 3 Comparative Example 3 Pressure sensitive adhesive layer 7 Example 4 Pressure sensitive adhesive layer 4 Comparative Example 4 Pressure sensitive adhesive layer 8 Comparative Example 5 Pressure sensitive adhesive layer 9 Comparative Example 6 Pressure sensitive adhesive layer 10

[0051] The above UV adhesive tapes were tested as follows:

[0052] 1. Peel force test: Test reference standard GB / T 2792-2014, UV irradiation intensity is 230mW / cm 2 , the irradiation time is 8s.

[0053] 2. Acid resistance test: stick the UV viscosity-reducing adhesive on the stainless steel plate at 180°, then soak it in acid solution for 30 minutes, take it out and wipe the surface solution dry, refer to GB / T 2792-2014, and test the peeling force before and after curing again. The acid solution is a 1:1 mixture of 3 mol / L HCL and 3 mol / L HF.

[0054] 3. Alkali resistance test: The test method is the same as the acid resistance test, the only difference is that the acid is replaced by alkali, which is a 3 mol / L NaOH aqueous solution.

[0055] 4. Residual glue rate: When testing the acid resistance test, refer to GB / T 2792-2014 for the residual glue rate test.

[0056] The above test results are shown in Table 3.

[0057] Table 3 Test results

[0058]

[0059] From the test results of the embodiments and comparative examples shown in Table 3, it can be concluded that the UV anti-tack tape provided by the present invention has high initial tack, excellent acid and alkali resistance stability, and good glass effect after UV irradiation and anti-tack, and is non-adhesive. The present invention adjusts the peeling force and corrosion resistance of the prepared UV anti-tack tape by adjusting the resin structure and cross-linking degree of the UV pressure-sensitive adhesive in the UV anti-tack tape; and prepares UV anti-tack tapes with different acid and alkali corrosion resistance and peeling strength by adjusting the addition amount of cholesteryl fluoride and the type of photoinitiator.

[0060] Although the addition of fluorinated monomers can improve the acid and alkali resistance of acrylic pressure-sensitive adhesives, the addition of general fluorinated monomers alone will affect the cross-linking of the resin due to their large polarity, resulting in a decrease in initial adhesion, such as in Comparative Example 6. However, the present invention modifies the fluorinated monomers into cholesteric fluoride and cooperates with the combined action of a composite photoinitiator to prevent the UV adhesive tape from migrating or polymerizing in an acid-base environment, and the initial adhesion can still reach 1100gf / 25mm after acid-base immersion. After curing, the adhesive is reduced and no adhesive residue is left, which is a technological advancement.

[0061] The present invention can also have many other embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications based on the present invention, but these corresponding changes and modifications should all fall within the scope of protection of the claims attached to the present invention.

Claims

1. A highly stable UV anti-viscosity tape, comprising a release layer, a UV anti-viscosity pressure-sensitive adhesive layer and a substrate layer; characterized in that: The UV viscosity-reducing pressure-sensitive adhesive layer is made of the following raw materials in parts by mass: 70-80 parts of polyacrylic acid-butadiene resin, 15-40 parts of cholesteryl fluoride, 2-5 parts of leveling agent, 0.5-5 parts of photoinitiator, 1-3 parts of curing agent, and 55-90 parts of solvent.

2. The UV adhesive tape according to claim 1, characterized in that: The polyacrylic acid-butadiene resin is a polymer obtained by copolymerization of acrylic acid and butadiene; the content of butadiene component in the polyacrylic acid-butadiene resin is 30-40%.

3. The UV anti-viscosity tape according to claim 1, characterized in that: The preparation method of the cholesterol fluoride comprises: Step 1: Take 5-norbornene-2-yl chloride and heat it with 4-(trifluoromethyl)benzyl alcohol to obtain (5-norbornene-2-carboxylic acid)-4-(trifluoromethyl)benzyl ester, hereinafter referred to as intermediate 1; Step 2: Intermediate 1 and cholesterol are added under acidic conditions to obtain cholesterol fluoride.

4. The UV adhesive tape according to claim 1, characterized in that: The photoinitiator is selected from any one or a combination of at least two of benzil dimethyl ether, dialkoxy acetophenone, methyl benzoylformate, 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 2-methyl-1-(4-methylthiophenyl)-2-morpholine-1-propanone, 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinebenzylphenyl)butanone, 2,4,6-trimethylbenzoylphenylphosphine, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester, benzophenone, 4,4'-bis(diethylamino)benzophenone, 2-isopropylthioxanthone and 4-dimethylamino-ethyl benzoate.

5. The UV anti-viscosity tape according to claim 1, characterized in that: The UV viscosity-reducing pressure-sensitive adhesive layer is made of the following raw materials in parts by mass: 70-80 parts of polyacrylic acid-butadiene resin, 20-30 parts of cholesterol fluoride, 2-3 parts of leveling agent, 0.5-3 parts of photoinitiator, 1-3 parts of curing agent, and 60-78 parts of solvent.

6. The UV anti-viscosity tape according to claim 1, characterized in that: The UV anti-viscosity tape comprises a release layer, a UV anti-viscosity pressure-sensitive adhesive layer and a substrate layer from top to bottom.

7. The UV anti-viscosity tape according to claim 1, characterized in that: The UV anti-viscosity tape comprises a release layer, a UV anti-viscosity pressure-sensitive adhesive layer, a substrate layer, a UV anti-viscosity pressure-sensitive adhesive layer and a release layer from top to bottom.

8. The UV adhesive tape according to claim 1, characterized in that: The preparation method of the UV viscosity-reducing pressure-sensitive adhesive layer comprises: Step 1: Add the leveling agent and photoinitiator to a vacuum centrifugal high-speed disperser, stir under vacuum, and dissolve completely; Step 2: Add the polyacrylic acid-butadiene resin into the disperser in step 1, stir under vacuum, seal and let stand; Step 3: Add the above-mentioned cholesterol fluoride and curing agent into a disperser, continue vacuum stirring, centrifuge and degas in a syringe, and vacuum seal with an aluminum foil bag to prepare the UV viscosity-reducing pressure-sensitive adhesive layer.

9. The UV adhesive tape according to claim 1, characterized in that: The thicknesses of the release layer, UV viscosity-reducing pressure-sensitive adhesive layer and substrate layer are 50±2 μm, 100±10 μm and 25±2 μm respectively.

10. The method for preparing the UV anti-viscosity tape according to any one of claims 1 to 9, characterized in that: include: The UV viscosity-reducing pressure-sensitive adhesive layer is coated on the surface of the substrate, and then a release agent is coated on the outer side of the UV viscosity-reducing pressure-sensitive adhesive layer to prepare a release layer, thereby obtaining a UV viscosity-reducing tape.

Citation Information

Patent Citations

  • Acid and alkali resistant UV visbreaking composition, UV visbreaking film and preparation method thereof

    CN108300352A